The Sensitivity of Arterial Spin-Labeling Imaging for Detection of Head and Neck Paragangliomas - Yu, Yannan; Tsui, Brian Q.; Glastonbury, Christine M.; Wu, Xin (Cynthia) (American Journal of Neuroradiology, 2025)
BACKGROUND AND PURPOSE: Head and neck paragangliomas (HNPGs) are rare neuroendocrine tumors whose hypervascular nature allows differentiation from many other head and neck neoplasms. We aimed to investigate the sensitivity of arterial spin-labeling (ASL) MR sequences for the detection of HNPGs.MATERIALS AND METHODS: All head and neck MR examinations performed at a single tertiary institution between 2015 and 2023 were searched. Studies using ASL sequences that indicated either clinical suspicion for or ultimate imaging diagnosis of HNPG were identified. These studies were independently reviewed by 2 neuroradiologists blinded to the original radiology reports to determine, in a stepwise fashion, the following: 1) whether there was asymmetrically elevated blood flow on ASL imaging, 2) whether ASL findings correlated with lesions identifiable on conventional anatomic images, and 3) whether lesions likely reflected paragangliomas on the basis of correlations with clinical, laboratory, pathology, and other radiology data (Disagreement between raters was resolved by consensus.). The Cohen κ coefficient and the sensitivity of ASL in identifying HNPGs were calculated.RESULTS: Eighty-four patients were included in the analysis (mean age, 54 [SD, 14] years and 47 women). Thirty patients had lesions confirmed or found likely to be HNPG, and 54 patients had lesions found unlikely to be HNPG or had no identifiable lesion. Among 46 of 84 patients with ASL blood flow asymmetry, 43 (93%) had lesions correlated with a lesion identifiable on anatomic imaging. Asymmetrically elevated ASL blood flow that correlated with a lesion demonstrated a sensitivity of 100% for reader A and 97% for reader B for identifying HNPG. The Cohen κ coefficient was 0.90 (SD, 0.11) between the 2 readers (P < .001). Among 18 cases with pathology- or dotatate PET–proved HNPG, the sensitivity was 100% for reader A and 94% for reader B.CONCLUSIONS: Asymmetrically elevated blood flow on ASL imaging demonstrates high sensitivity for the detection of HNPG, with almost perfect interrater agreement.ASLarterial spin-labelingHNhead and neckHNPGhead and neck paraganglioma